Estimating the long-term market shares in the Peruvian mobile telephony service: An application of the Markov Chains - Gavilano Aspillaga, Manuel (2019)
This brief document shows in a simple and direct way the estimation of the market shares that mobile operators will have in the long term, understanding as a long term that situation in which the market shares oscillate in very small variations. To achieve this goal, the so-called Markov Chains are used, where the Transition Matrices are formed through the states of migration between companies using the Mobile Number Portability (PNM) process. The conclusions of this paper indicate that in the long term Telefónica del Perú will have the largest market share (36.4 %), followed by América Móvil, (35 %); and finally Entel (17.4 %) and Viettel (11.2 %).